Основні напрямки інтенсифікації технології чорного чаю - Червоткіна, Олександра Олександрівна; Тарасенко, Віра Григорівна; Chervotkina, Oleksandra; Tarasenko, Vira (Мелітополь : 2022, 2022)
UA: Постійно зростаючий попит на чай, як один з важливих продуктів харчування, створює необхідність пошуку резервів його виробництва, створення маловідходних, комплексних технологій, що неможливо без відповідної машинно-апаратурної переробки переробних підприємств, інтенсифікації та оптимізації технологічних та харчових переваг. продуктів чорного чаю, що є найбільш споживаними в нашій країні і в ближньому зарубіжжі. Розроблені знову технології повинні забезпечити поліпшення якості, біологічної цінності біохімічного контролю чайного виробництва, метод штучного зав'ялювання, технологія чорного чаю із застосуванням термічної обробки недоферментованого напівфабрикату, роздільна переробка чайного листа. Крім того розроблено технології сухих та рідких чайних концентратів. EN: The production of black tea is based on oxidative processes that take place in the destroyed cells of the tea leaf, as a result of which substances are formed that determine the specificity of the product. Therefore, the main task of intensification in the production of black tea is the maximum and simultaneous destruction of the anatomical integrity of leaf cells in order to make the most of its potential and ensure the uniformity of oxidative transformations. Cell disintegration can be caused by various damaging factors: physical, mechanical, chemical, biological, as well as various combinations thereof. These techniques provide a change in the direction of biochemical processes occurring in fresh tea leaves, resulting in conditions for the development of oxidative processes, which depend on the formation of quality indicators of finished products. The ever-increasing demand for tea, as one of the important food products, creates the need to find reserves for its production, create low-waste, integrated technologies, which is impossible without proper processing of processing plants, intensification and optimization of technological and food benefits. black tea products, which are most consumed in our country and abroad. Newly developed technologies should improve the quality, biological value of biochemical control of tea production, the method of artificial wilting, black tea technology using heat treatment of unfermented semi-finished products, separate processing of tea leaves. In addition, technologies for dry and liquid tea concentrates have been developed.
Main directions of intensification of black tea technology
Червоткіна О. О., Тарасенко В. Г. Основні напрямки інтенсифікації технології чорного чаю. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 2. C. 200-211.
Keywords: гранулювання; чорний чай; ферментація; чайне листя; подрібнення; переробка дрібних фракцій чайного листя; granulation; black tea; fermentation; tea leaves; grinding; processing of small fractions of tea leaves